Prediction by a Genetic Algorithm of the Fiber-Matrix Interface Damage for Composite Material. Part 2. Study of Shear Damage in Graphite/Epoxv Nanocomposites - Mokaddem, A.; Alami, M.; Ziani, N.; Bcldjoudi, N.; Boutaous, A. (Проблемы прочности, 2014)
The objective in this paper is to apply the same genetic model as applied in Part 1 to optimizing the shear damage to the fiber–matrix interface of nanocomposite material graphite epoxy. The results show good agreement between the numerical simulation and the actual behavior of the material chosen composite and nanocomposites, and these results are similar to results obtained by processing techniques expanded graphite reinforced polymer nanocomposites made by Asma Yasmine. These results were confirmed by calculating the rate of damage with a genetic simulation. Описанная в сообщении 1 генетическая модель используется для оптимизации повреждения в плоскости максимальных сдвиговых напряжений на стыке волокон и матрицы в нанокомпозитном графито-эпоксидном материале. Получена хорошая корреляция между численными расчетами и экспериментальными данными для композита и нанокомпозитов на основе графита, усиленного нанополимерами. Экспериментальные данные также хорошо согласуются с результатами, полученными на основании расчетной методики Ясмина. В дальнейших исследованиях планируется изучение влияния термических напряжений на подобную оптимизацию. Описана в повідомленні 1 генетична модель використовується для оптимізації пошкодження в площині максимальних зсувних напружень на стику волокон і матриці в нанокомпозитному графіто-епоксидному матеріалі. Отримано хорошу кореляцію між числовими розрахунками й експериментальними даними для композита та нанокомпозит ів на основі графіту, підсиленого нанополімерами. Експериментальні дані також добре узгоджуються з результатами, що отримані на основі розрахункової методики Ясміна. У подальших дослідженнях планується вивчення впливу термічних напружень на подібну оптимізацію.